Insights to bioprocess and treatment competence of urban wetlands. (15th January 2018) - Mahapatra, Durga Madhab; Joshi, N.V.; Ramachandra, T.V.
Abstract: Wetlands play a major role in the recharge of groundwater resources, maintenance of water quality (remediation), moderate microclimate while supporting local livelihood through provision of fish, fodder, etc. The present study aims to investigate algal-bacterial consortium as a function of residence time with the water quality dynamics in two major wetlands in Bangalore city, India. Over thirty-two genera of algae were recorded with more than 40 species in the lakes and two dominant bacterial assemblages. The higher Ammonium-N content favoured the growth of these members. Significant correlation was observed between the nutrient concentrations and the community structure at the inflows and the outflows. The algal community showed negative correlation to filterable COD and high nutrients levels while bacterial abundance was observed under high loadings. The green algae Chlorophyceae ( Chlorella blooms), which are indicators of nutrient enrichment were observed predominantly, that needs an immediate attention. Higher overall treatment efficiency was observed in terms of CNP removal during the Pre-monsoon season attributed to absence of macrophytes cover and rapid growth of algal assemblage's due to higher temperature regimes with adequate solar insolation. Graphical abstract: Image 1 Highlights: The treatment competence of the wastewater fed urban lakes is assessed. Algal-bacterial communities helps in the remediation, mainly Ammonium-Nitrogen. Flow cytometry is used as an efficient tool for bacterial analysis. New Treatment Index is proposed considering solids, nutrients and bacterial counts. Pre-monsoon plays a major role in governing the overall wetland's water quality.